Direct Behavior Rating Instrumentation: Evaluating the Impact of Scale Formats. (March 2017) - Miller, Faith G.; Riley-Tillman, T. Chris; Chafouleas, Sandra M.; Schardt, Alyssa A.
The purpose of this study was to investigate the impact of two different Direct Behavior Rating–Single Item Scale (DBR-SIS) formats on rating accuracy. A total of 119 undergraduate students participated in one of two study conditions, each utilizing a different DBR-SIS scale format: one that included percentage of time anchors on the DBR-SIS scale and an explicit reference to duration of the target behavior (percent group) and one that did not include percentage anchors nor a reference to duration of the target behavior (no percent group). Participants viewed nine brief video clips and rated student behavior using one of the two DBR-SIS formats. Rating accuracy was determined by calculating the absolute difference between participant ratings and two criterion measures: systematic direct observation scores and DBR-SIS expert ratings. Statistically significant differences between groups were found on only two occasions, pertaining to ratings of academically engaged behavior. Limitations and directions for future research are discussed.